Back Cover. (17th April 2020) - Stauder, Reinhard; Lambert, Jérémy; Desruol‐Allardin, Sandra; Savre, Isabelle; Gaugler, Lona; Stojkov, Igor; Siebert, Uwe; Chevrou‐Séverac, Hélène
Abstract : The back cover image is based on the Original Article* Patient‐reported outcome measures in studies of myelodysplastic syndromes and acute myeloid leukemia: Literature review and landscape analysis by Reinhard Stauder** et al., https://doi.org/10.1111/ejh.13389 .***